2011
DOI: 10.1111/j.1471-0528.2011.02977.x
|View full text |Cite
|
Sign up to set email alerts
|

Should births be centralised in higher level hospitals? Experiences from regionalised health care in Finland

Abstract: Objective To describe: (i) trends in centralisation and unplanned out-of-hospital births; (ii) perinatal mortality by place of birth; and (iii) health and birth outcomes in areas served by hospitals of different levels.Design Cross-sectional analysis of medical birth register data. Methods In the hospital-based analysis, birthweight was adjusted by logistic regression. In the area-based analysis results were calculated according to where women lived, grouping them into areas served by different hospitals. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 32 publications
0
66
2
3
Order By: Relevance
“…This negates the positive effect of centralization, since perinatal mortality rate in unplanned out-ofhospital deliveries is shown to be at least twofold compared to hospital deliveries [12]. Also, a recent Finnish study showed that by decreasing the number of delivery units from 49 to 34, the rate of unplanned out-of-hospital deliveries doubled in two decades [8]. In addition, perinatal and neonatal deaths are associated with the most expensive instances of compensation regarding patient injuries [13].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…This negates the positive effect of centralization, since perinatal mortality rate in unplanned out-ofhospital deliveries is shown to be at least twofold compared to hospital deliveries [12]. Also, a recent Finnish study showed that by decreasing the number of delivery units from 49 to 34, the rate of unplanned out-of-hospital deliveries doubled in two decades [8]. In addition, perinatal and neonatal deaths are associated with the most expensive instances of compensation regarding patient injuries [13].…”
Section: Commentmentioning
confidence: 99%
“…In contrast to preterm newborns, conclusions in studies on low-risk deliveries are incoherent [5]. Some studies have shown better outcomes for deliveries in tertiary hospitals [6,7] whereas others have not [8,9]. Also, current clinical practice varies among countries, thus making comparisons difficult.…”
Section: Introductionmentioning
confidence: 95%
“…Delivery at hospitals with low delivery volumes has been correlated with better, worse and comparable pregnancy outcomes compared with delivery at larger centres, [1][2][3][4][5][6][7] and studies examining the safety of delivery at rural versus urban hospitals have likewise produced conflicting results. [8][9][10][11][12] Establishing the relative safety of obstetric care in small rural hospitals is challenging.…”
mentioning
confidence: 99%
“…Adjustment for maternal risk factors is unlikely to completely account for case-mix differences. Comparisons made according to catchment area (in which women are classified according to their place of residence) 1,2,4,[8][9][10][11][12] prevent bias due to referral patterns, but confounding by differences in socioeconomic status and health behaviours between women living in urban and rural areas remains a concern.10 Such comparisons also have less utility for decisions about service regionalization because the policy option is not to change rural women's place of residence to an urban setting, but rather to have rural women travel to an urban setting to deliver, which may lead to increased risks, such as unintentional out-of-hospital delivery. Since 1998, nearly one-third of hospitals in British Columbia, Canada, have stopped providing planned obstetric services.…”
mentioning
confidence: 99%
See 1 more Smart Citation